Associations Between the Purinergic Receptor P2X7 and Leprosy Disease - Souza, Rebeka da Conceição; Louvain de Souza, Thaís; Ferreira, Cristina dos Santos; Nascimento, Letícia Silva; Nahn, Edilbert Pellegrini; Peixoto-Rangel, Alba Lucínia (Frontiers in Genetics, 2021)
Leprosy is an infectious disease still highly prevalent in Brazil, having been detected around 27,863 new cases in 2019. Exposure to Mycobacterium leprae may not be sufficient to trigger the disease, which seems to be influenced by host immunogenetics to determine resistance or susceptibility. The purinergic receptor P2X7 plays a crucial role in immunity, inflammation, neurological function, bone homeostasis, and neoplasia and is associated with several infectious and non-infectious diseases. Here, we first compare the P2RX7 expression in RNA-seq experiments from 16 leprosy cases and 16 healthy controls, in order to establish the magnitude of allelic-specific expression for single nucleotide polymorphisms (SNPs) of the gene P2RX7 and to determine the level of gene expression in healthy and diseased skin. In addition, we also evaluated the association of two P2RX7 SNPs (c.1513A>C/rs3751143 and c.1068A>G/rs1718119) with leprosy risk. The expression of P2RX7 was found significantly up-regulated at macrophage cells from leprosy patients compared to healthy controls, mainly in macrophages from lepromatous patients. Significant risk for leprosy disease was associated with loss function of rs3751143 homozygous mutant CC (CC vs. AA: p=0.001; Odds ratio=1.676, 95% CI=1.251-2.247) but not with heterozygous AC (AC vs. AA: p=0.001; Odds ratio=1.429, 95% CI=1.260-1.621). Contrary, the polymorphic A allele from gain function of rs1718119 was associated with protection for the development of leprosy, as observed in the dominant model (AA+AG x GG p=0.0028; Odds ratio=0.03516; CI=0.1801-0.6864). So, our results suggest that the functional P2X7 purinergic receptor may exert a key role in the Mycobacterium death inside macrophages and inflammatory response which is necessary to control of disease.